Induction of labour and its outcome in a Teaching Hospital. - Rathnayaka, K.P.J (My University, 2004)
This prospective observational study was carried out in the Teaching Hospital, Galle. -The rate of IOL was 11.6 percent. The three leading indications for IOL were past dates (61 percent ), pre labor rupture of membranes (20 percentage) and pregnancy induced, hypertension (9 percent). A specialist decided on the IOL in 58 percent of cases. The outcome of IOL was not affected by the grade of the medical officer making the decision. Stripping, of membrans (SM) was carried out in 300 (44.5 percent) and Foley's catheter (FC) was inserted in 82 (12.2 percent) of women for ripening of cervix before IOL. The emergency caesarean section (CS) rate of 15.3 percentage after IOL was significantly higher than the emergency CS rate after spontaneous labor (10.4 percent , p005). Although IOL at 40-41 weeks gestation had a higher CS rate (17.2 percent) compared to that at 41 plus weeks of gestation (12.4 percent) It was statistically not significant.